Arm Abduction Provides a Better Reduction of the Bankart Lesion During Immobilization in External Rotation After an Initial Shoulder Dislocation. (July 2015) - Itoi, Eiji; Kitamura, Toshio; Hitachi, Shin; Hatta, Taku; Yamamoto, Nobuyuki; Sano, Hirotaka
Background: Shoulder dislocation often recurs, especially in the younger population. Immobilization in external rotation, in which a Bankart lesion is displaced in the anterior, medial, and inferior directions, was introduced as a new method of nonoperative treatment, but its clinical efficiency is controversial. In terms of reducing the lesion, it is reasonable to incorporate not only external rotation, which makes the anterior soft tissues tight to push the lesion posteriorly and laterally, but also abduction, which makes the inferior soft tissues tight to push the lesion superiorly. Hypothesis: Abducting the arm during immobilization in external rotation will improve the reduction of a Bankart lesion. Study Design: Controlled laboratory study. Methods: There were 37 patients with initial shoulder dislocation enrolled in this study. After reduction, MRI was taken in 4 positions of the shoulder: adduction and internal rotation (Add-IR), adduction and external rotation (Add-ER), 30° of abduction and 30° of external rotation (Abd-30ER), and 30° of abduction and 60° of external rotation (Abd-60ER). On radial slices, the separation, displacement of the labrum, and opening angle of the capsule were measured. Results: Add-ER improved the reduction of the anterior labrum but not the inferior labrum when compared with Add-IR. Both Abd-30ER and Abd-60ER improved the reduction of the inferior labrum as compared with Add-IR. Furthermore, Abd-60ER improved the reduction more than Add-ER. Conclusion: Among the 4 positions tested, Abd-60ER is the best position in terms of reducing the Bankart lesion. Clinical Relevance: Abducting the shoulder during immobilization in external rotation is demonstrated to improve the reduction of the Bankart lesion. Therefore, this position is expected to reduce the recurrence rate after initial dislocation of the shoulder. Future clinical trials are necessary.